La muerte digna bajo la jurisprudencia del derecho internacional de los derechos humanos - Miró Quesada Gayoso, Josefina (2020)
Currently, the right to die with dignity has come to the forefront in the Peruvian political debate since the domestic legal framework not only denies this right to whom aims to exercise, but penalizes it. However, when transcending this legal framework, the outlook varies.This article explores the scope and content of the human rights that underpin the right to die with dignity exercised by a conscious person in full mental faculties requesting to put an end to its life due to intolerable pain suffered as a result of an incurable disease. Based on the study of international instruments of human rights protection, as well as the jurisprudence of the Inter-American Court of Human Rights, it is argued that one’s faculty to intervene in one’s life not only does not constitute a violation of international obligations of States Parties to treaties such as the American Convention, but represents the respect and guarantee of such rights.